Regarding marxism - Panasiuk, Ryszard (Hybris, 2017)
My paper refers to Leszek Kołakowski’s Main Currents of Marxism: Its Origin, Growth, and Dissolution (Oxford: Clarendon Press 1987). Kołakowski’s intention was to write a textbook on the history of Marxism based on his lectures but his book is much more than that. It is a philosophical treatise in which Marx’s doctrine of mankind and the program of its liberation are critically analysed and reinterpreted. The core of Marx’s philosophy is the idea of man and the belief that the real existence of humans is not identical with their essence. Kołakowski shows that this belief is rooted in mythological thinking, the Platonic tradition, and in the Christian thought. A moral that follows from Kołakowski’s critical analysis of Marx’s doctrine is that man has never lived in a paradise and yet he perceives himself as banished thereof; that he will never enter a paradise and yet he cannot live without the faith that this is somehow possible. Therefore, what he should do is to have a minimum of common sense and skepticism related to it, for they would protect him against the traps laid by false prophets repeatedly asserting that they know the means to construct the paradise today or at least tomorrow.